Efektivitas Model Pembelajaran Problem Possing Berbantuan Edmodo terhadap Pemahaman Konsep Ditinjau dari Keterampilan Proses Sains dan Keterampilan Berpikir Kritis - Franciska Ayunungsih Ratnawati (Jurnal Dedikasi Pendidikan, 2020)
The use of science process skills plays a significant role in supporting students' abilities in terms of critical thinking or conceptual understanding. Especially in the 21st-century learning era, the demand for critical thinking is very much needed and supported by the use of satisfactory technology. The purpose of this study is to describe the effect of problem possing learning models on understanding concepts in terms of science process skills and critical thinking skills. This study was made in the form of a quasi-experimental design with a pretest-posttest control group design model with a research location at SMAN 1 Gamping Sleman. The research sample consisted of 2 classes, and each class consisted of 28 students, with the topic being taught that there was dynamic fluid. The research instrument used was a test sheet conceptual understanding and critical thinking skills, as well as questionnaires science process skills. The study results showed that the model-assisted learning Edmodo Problem Posing on the fluid dynamic topic could improve students' understanding of concept skills in terms of science process skills and critical thinking proven by the difference in posttest scores between the experimental class and the control class with a standard N-gain of 0.50 and 0.20. The ability to understand concepts in the dynamic fluid material of the experimental class is significantly higher than the control class. Based on the calculation results of an analysis of covariance (ANCOVA) obtained value of Fcount = 9.835 and Ft5% = 4.03, because Fcount> Ft 5% then the null hypothesis is rejected so that there is an effect of increasing the ability of students to understand the concept of the given treatment learning with Edmodo-assisted Problem Posing and conventional learning with Edmodo in terms of science process skills and critical thinking. There is a contribution of covariate variable with a value of R2y (1,2,3) = 0,2658 with three covariates viz science process skills, critical thinking and initial abilities that provide science process skills by 22.85%, critical thinking by 2.37%, and initial ability by 1.37%.